Impact of the Mental Toughness Training Circle on the psychological aspects of athletes in situational sports: a pilot experiment - Putra, Miftah Fariz Prima; Sutoro, Sutoro; Sinaga, Evi; Hidayat, Rodhi R; Wanena, Tery; Wandik, Yos; Ridwan, Mochamad; Destriana, Destriana; Jannah, Miftakhul; Priambodo, Anung; Juriana, Juriana; Tahki, Kurnia; et al. (Zdorov'i︠a︡, sport, reabilitat︠s︡ii︠a, 2025)
Purpose. This study aims to evaluate the effect of providing Mental Toughness Training Circle mental training on athletes' mental toughness, performance, religiosity, anxiety, satisfaction, and happiness in life. Material and methods. The randomized experimental design was used to evaluate Mental Toughness Training Circle. A total of 31 college-level athletes were involved and divided into two groups. Six important constructs related to athletes' psychological aspects, including mental toughness, performance, religiosity, anxiety, satisfaction, and athlete happiness are measured using the Mental Toughness Inventory, Self-Assessment of Athletics Performance, Spirituality in Sports Test, Sports Anxiety Scale-2, Social Validation Questionnaire, and Satisfaction with Life Scale. Results. The research findings prove that the Mental Toughness Training Circle mental training program has a significant effect on athletes' mental toughness, performance, anxiety, religiosity, satisfaction, and life happiness. Apart from that, this study also shows that the application of Mental Toughness Training Circle can increase positive emotional dimensions (mental toughness, performance, religiosity, satisfaction, and happiness) and reduce negative emotions (anxiety) in athletes. Conclusions. The implications of this study show that Mental Toughness Training Circle can be used by athletic trainers and mental coaches to improve the quality of athletes, especially in psychological or mental aspects. Цель. Целью данного исследования является оценка влияния психологической тренировки в рамках программы «Круг обучения психологической стойкости» на психическую стойкость, работоспособность, религиозность, тревожность, удовлетворенность и счастье спортсменов в жизни. Материал и методы. Рандомизированный экспериментальный план использовался для оценки кружка тренировки психической стойкости. Всего в нем принял участие 31 спортсмен колледжа, которые были разделены на две группы. Шесть важных показателей, связанных с психологическими аспектами спортсменов, включая психологическую стойкость, работоспособность, религиозность, тревогу, удовлетворенность и счастье спортсмена, измеряются с использованием Опросника психической стойкости, самооценки спортивных результатов, теста духовности в спорте, шкалы спортивной тревожности-2, Анкета социальной валидации и Шкала удовлетворенности жизнью. Полученные результаты. Результаты исследования доказывают, что программа умственной тренировки «Круг обучения психологической стойкости» оказывает существенное влияние на психическую стойкость, работоспособность, тревожность, религиозность, удовлетворенность и счастье в жизни спортсменов. Кроме того, это исследование также показывает, что применение «Круга обучения психологической стойкости» может повысить положительные эмоциональные аспекты (умственная устойчивость, работоспособность, религиозность, удовлетворение и счастье) и уменьшить отрицательные эмоции (тревогу) у спортсменов. Выводы. Результаты этого исследования показывают, что тренировочный цикл «Круга обучения психологической стойкости» может использоваться спортивными тренерами и тренерами по психологии для улучшения качеств спортсменов, особенно в психологических или умственных аспектах. Мета. Метою даного дослідження є оцінка впливу психологічного тренування в рамках програми «Коло навчання психологічної стійкості» на психічну стійкість, працездатність, релігійність, тривожність, задоволеність та щастя спортсменів у житті. Матеріал та методи. Рандомізований експериментальний план використовувався з метою оцінки гуртка тренування психічної стійкості. Загалом у ньому взяв участь 31 спортсмен коледжу, які були поділені на дві групи. Шість важливих показників, пов'язаних з психологічними аспектами спортсменів, включаючи психологічну стійкість, працездатність, релігійність, тривогу, задоволеність і щастя спортсмена, вимірюються з використанням Опитувальника психічної стійкості, самооцінки спортивних результатів, тесту духовності у спорті, шкали спортивної тривожності та Шкала задоволеності життям. Отримані результати. Результати дослідження доводять, що програма розумового тренування «Коло навчання психологічної стійкості» істотно впливає на психічну стійкість, працездатність, тривожність, релігійність, задоволеність і щастя у житті спортсменів. Крім того, це дослідження також показує, що застосування «Кола навчання психологічної стійкості» може підвищити позитивні емоційні аспекти (розумова стійкість, працездатність, релігійність, задоволення та щастя) та зменшити негативні емоції (тривогу) у спортсменів. Висновки. Результати цього дослідження показують, що тренувальний цикл «Кола навчання психологічної стійкості» може використовуватися спортивними тренерами та тренерами з психології для покращення якостей спортсменів, особливо у психологічних чи розумових аспектах.